Resistência negra no círculo de cultura sociopoético: pretagogia e produção didática para implementação da Lei 10.639/03 no projovem urbano - Alves, Maria Kellynia Farias (2015)
This research deals with the reflections from an adult education teacher training experience in order to develop strategies to strengthen the implementation of Law 10.639 / 03 under the National Programme of young Inclusion - Projovem Urban in view of ‘pretagogia’, the Afro-descendant and didactic production oral literature. Research shows that most students in adult education, particularly programs like Projovem, self-claim blacks. This type of education has been marked by social inequalities arising and racism in its different forms. Law 10.639 / 03 which deals with the mandatory teaching of history and african-Brazilian and African culture is a way to highlight the importance of black culture in the formation of Brazilian society, still finding challenges to its implementation in adult education. The study subjects are the students and teachers of Urban Projovem two schools on the outskirts of Fortaleza and a group of graduate students in Pedagogy UFC. The motivations that led to the need to turn to the ethnic-racial issue in ProJovem Urban involve from the family environment to the very public characteristics attended by Projovem Urban. The theoretical reference is based on the production of Petit (2001, 2009), Petit, Silva (2011), Cunha (2010.2011), Gomes (2012, 2003), Munanga (2010.2000), Silva (2003), DeFrantz (2004), Oliveira (2005, 2003, 2008), among others, to guide our reflections. The methodological approach has social poetics as inspiration, as it is a way to experience the research in its collective approach and the various artistic languages through ‘sociopoetizados’ culture circles and theme generator black resistance. The survey results revealed that students and teachers experience different perspectives on ethnic-racial issue at school, moving between silencing, denials and statements about the ethnic and racial origin and the black resistance which led us to develop the concept of african belonging. Markers of Africanities, the African oral literature, Pretagogia and didactic production is presented as potentiating other forms of teaching in adult education. It is concluded that research bridges the gap between bodies-territories through the culture circles and the Pretagogia, being important for the didactic reinvention practices of teachers in adult education to promote the change of attitude towards the ethnic-racial relations, generating other implications with the theme. So you can rethink practices, curriculum and learning to revisit the Africanities and enable the implementation and afroreferenciada didactic production.